Hubungan Mengonsumsi Makanan Cepat Saji (Fast Food) Dengan Kejadian Dysmenorrhea Pada Remaja Putri - Simbung, Rismawati; Ohorella, Fadjriah; Metasari, Nova Ulfa (Madu : Jurnal Kesehatan, 2023)
Fast food is generally preferred by teenagers, as well as adults because it tastes according to taste and is affordable. In a broad sense, fast food actually includes all types of food that can be served quickly. The presence of fast food greatly affects the diet of teenagers in big cities. It is undeniable that with a practical city lifestyle, teenagers find it difficult to avoid fast food. The purpose of this study was to find the relationship between fast food consumption and the incidence of primary dysmenorrhea in adolescent girls at SMA Negeri 12 Makassar in 2020. In this study, samples were taken from 35 young women used Accidental Sampling technique. The results showed that from 35 respondents as samples, 21 people used fast food (60.0%) and 14 people did not use fast food (40.0%). The results showed that of the 35 respondents who were sampled, 19 people had dysmenorrhea (54.3%) and 16 people did not experience dysmenorrhea (45.7%). The results showed that there was a relationship between consumption of fast food and the incidence of primary dysmenorrhea in female adolescents at SMA Negeri 12 Makassar